Asuhan Kebidanan Komprehensif Pada Ny “F” G3P2A0 Dengan Risiko Tinggi Usia Terlalu Tua (40 Tahun) di Praktek Mandiri Bidan Dewi Ciselia Tahun 2024 - Ciselia, Dewi; Anggraini, Ririn; Saputra, Andre Utama (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Integrated antenatal care is a comprehensive and quality antenatal service provided to all pregnant women. Complete antenatal examinations are K1, K2, K3 and K4.). This research was carried out in the health sector which directly focuses on Comprehensive Midwifery Care for High Risk Pregnant Women who are Too Old at the Independent Practice of Midwife Dewi Ciselia. The location for taking cases is the place where the case is taken. The location of this Midwifery Care is carried out at the Independent Practice of Midwife Dewi Ciselia. The implementation time is the time limit at which the case is taken. This care was carried out in January - February 2024. The tools used were as follows. Tools and materials for data collection: High risk midwifery care format, stationery. Tools and materials for physical examination and observation: weight scales, height measuring equipment. Tensimeter Thermometer, Watch, Mettlin monocular stethoscope, Hummer reflex, Partus set, Heating set Infusion set. Tools and Materials for documenting patient status and medical records Existing documents Stationery. The number of samples for this study was 4 pregnant women at high risk of being too old. This research was conducted in January - February 2024. The results of the research were that the mother understood and felt happy about the results of her and her baby's examination, the mother knew and understood everything the midwife had explained and was willing to follow what the midwife suggested.